THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND EMPLOYEE ENGAGEMENT IN UD EMPLOYEES. HEALTHY BEAUTY GORONTALO - Mansyur, Novita Sari; Ntobuo, Fendi; Mursyid, Muhammad; Kamuli, Fahri (Universitas Negeri Gorontalo, 2025)
This study was conducted to examine the extent of the relationshipbetween organizational culture and employee engagement in employeesat UD. Sehat Indah Gorontalo by using a quantitative approach through thecorrelational method. All employees totaling 60 people were used as aresearch sample using the total sampling technique. Data analysis wascarried out through normality tests, linearity tests, and Pearson ProductMoment correlation with the help of SPSS software version 20. The resultsshowed that there was a positive and significant relationship betweenorganizational culture and employee engagement with a correlationcoefficient value of 0.419 at a significance level of p equal to 0.000 whichis smaller than 0.05. These findings confirm that the quality oforganizational culture makes a real contribution to employee engagementlevels. The novelty of this research lies in the disclosure of the strength ofthe relationship between organizational culture and employeeengagement in the context of local medium-sized business organizationswhich has been limited to empirical research. In addition, the results ofthe categorization showed that as many as eight employees or around 13.1percent were in the medium category in the perception of organizationalculture. These findings show that there is a gap in the internalization oforganizational culture among employees. This condition has an impact onthe overall decline in the level of employee engagement, where theemployee engagement rate that was originally expected to reach onehundred percent decreased to 86.9 percent. These findings provide a newunderstanding that differences in perceptions of organizational culture,albeit in relatively small proportions, can affect the achievement ofcollective work engagement. This research not only confirms therelationship between organizational culture and employee engagement,but also makes a new contribution by affirming the importance ofconsistency and fairness in the implementation of organizational cultureas key factors